2012
DOI: 10.3389/fmicb.2012.00119
|View full text |Cite
|
Sign up to set email alerts
|

Integron Involvement in Environmental Spread of Antibiotic Resistance

Abstract: The spread of antibiotic-resistant bacteria is a growing problem and a public health issue. In recent decades, various genetic mechanisms involved in the spread of resistance genes among bacteria have been identified. Integrons – genetic elements that acquire, exchange, and express genes embedded within gene cassettes (GC) – are one of these mechanisms. Integrons are widely distributed, especially in Gram-negative bacteria; they are carried by mobile genetic elements, plasmids, and transposons, which promote t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
223
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(242 citation statements)
references
References 165 publications
12
223
0
7
Order By: Relevance
“…Recent functional metagenomic studies suggested that soil microbial phylogenetic and taxonomic structure is the primary determinant of ARG profile across various soil types, and no positive correlation was found between the soil ARGs and mobility elements suggesting that the horizontal gene transfer between soil bacteria is very low (Forsberg et al 2014). In fact, integrons are just one of the many types of mobile genetic elements involved in the adaptation of bacteria (Stalder et al 2012), and we did not find any positive effect of manure application on the transposase gene tnpA. Therefore, although the acquisition of ARGs by lateral gene transfer is considered as the most probable route of ARGs emergence in clinical environments (Nesme and Simonet 2014), such mechanism is pending more investigations in soil environments.…”
Section: Potential For Horizontal Gene Transfer Of Args In Manure-trementioning
confidence: 99%
See 2 more Smart Citations
“…Recent functional metagenomic studies suggested that soil microbial phylogenetic and taxonomic structure is the primary determinant of ARG profile across various soil types, and no positive correlation was found between the soil ARGs and mobility elements suggesting that the horizontal gene transfer between soil bacteria is very low (Forsberg et al 2014). In fact, integrons are just one of the many types of mobile genetic elements involved in the adaptation of bacteria (Stalder et al 2012), and we did not find any positive effect of manure application on the transposase gene tnpA. Therefore, although the acquisition of ARGs by lateral gene transfer is considered as the most probable route of ARGs emergence in clinical environments (Nesme and Simonet 2014), such mechanism is pending more investigations in soil environments.…”
Section: Potential For Horizontal Gene Transfer Of Args In Manure-trementioning
confidence: 99%
“…Integrons possess a site specific recombination system that could capture and express mobile gene cassettes (Heuer, Schmitt and Smalla 2011a), and they were reported to often localize in broad-host-range IncP-1ε plasmids with a wide distribution in agricultural systems that further facilitates their mobility potential (Heuer et al 2012;Jechalke et al 2014c;Wolters et al 2015). The critical roles of integrons in the dissemination of ARGs in environments have been highlighted by cultivation methods and metagenomics approaches (Hardwick et al 2008;Stalder et al 2012;Gillings et al 2015). Class 1 integrons have been extensively studied due to their widespread distribution in Gram-negative bacteria of clinical importance (Stalder et al 2012), and the intI1 genes were reported to be very common in soils and related ecosystems (Gillings et al 2008;Jechalke et al 2014c).…”
Section: Potential For Horizontal Gene Transfer Of Args In Manure-trementioning
confidence: 99%
See 1 more Smart Citation
“…The qac genes are commonly found on class 1 integrons, for example from clinical isolates (Gillings et al 2009;Stalder et al 2012). Class 1 integrons are able to accumulate, exchange, and express gene cassettes, which are known to carry resistance genes for almost all antibiotic families (Stalder et al 2012). These integrons are also widespread in the environment such as agricultural soils (Gillings et al 2014;Jechalke et al 2014).…”
Section: Role Of Qaacs In the Selection Of Antibiotic Resistancementioning
confidence: 99%
“…Bacterial pathogens carrying ARGs can survive in the presence of antibiotics through several mechanisms (Wright, 2012), thereby enriching resistant strains and lowering drug efficacy. A major concern is that ARGs can be shared among different species through horizontal gene transfer (Stokes and Gillings, 2011), which appears to be a rare, but important event in the spread of antibiotic resistance (Durso et al, 2012;Forsberg et al, 2014;Stalder et al, 2012). The rise in percentages of resistant bacteria has steadily followed the rise in antibiotic use in humans and agriculture.…”
Section: Introductionmentioning
confidence: 99%